Disembedding Polanyi: Exploring Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
The paper provides an introduction to a theme issue devoted to the influence—and the potential—of the work of Karl Polanyi in the field of economic geography. Polanyi has been an inspirational figure in the heterodox field of ‘socioeconomics’, where the inseparability of the economic and the social is taken to be axiomatic. He has also made recurrent appearances in economic geography since the early 1990s, as a progenitor of the ‘networks and embeddedness’ approach and in his role as a prescient critic of market fundamentalism. But the potential of Polanyian approaches in economic geography has only been fitfully explored. In this context, the contributions to this theme issue make the case for a more sustained—but also open, critical, and creative—engagement with Polanyi's legacy.
Keywords: economic geography; embeddedness